The Concept Of Silence After Ijab In Marriage Ceremonies: The Perspective Of Sheikh Muhammad Arsyad Al-Banjari In Kitab Nikah - Mohammad Ridwan; Fazri Rahmadani; Ahmad Risandi (Sharia Journal and Education Center Publishing, 2025)
The tradition of